2014
DOI: 10.1111/j.1532-950x.2014.12286.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Surgical and Medical Management of Cecal Impaction in 150 Horses (1991–2011)

Abstract: Compared to the recent reports, the proportion of horses alive at hospital discharge was lower for both medically and surgically managed horses with cecal impaction. There was decreased survival for horses treated medically than those treated surgically; however, no significant difference was seen in survival between horses managed with typhlotomy alone versus jejunocolostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 14 publications
0
25
0
1
Order By: Relevance
“…There are still few large‐scale, comprehensive studies investigating caecal disease. In recent studies of caecal impactions and intussusceptions, no breed predisposition was apparent, but also not explicitly investigated 26–31 . The results should therefore be interpreted with caution and larger studies are needed to determine whether horse type plays a role in the development of caecal disorders.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There are still few large‐scale, comprehensive studies investigating caecal disease. In recent studies of caecal impactions and intussusceptions, no breed predisposition was apparent, but also not explicitly investigated 26–31 . The results should therefore be interpreted with caution and larger studies are needed to determine whether horse type plays a role in the development of caecal disorders.…”
Section: Discussionmentioning
confidence: 96%
“…In recent studies of caecal impactions and intussusceptions, no breed predisposition was apparent, but also not explicitly investigated. [26][27][28][29][30][31] The results should therefore be interpreted with caution and larger studies are needed to determine whether horse type plays a role in the development of caecal disorders. The study suffered from several limitations, including the retrospective nature which is inherently associated with the problem of having to rely on the information written in the record.…”
Section: Papermentioning
confidence: 99%
“…There are few reports in the literature regarding the re-introduction of feed and water following resolution of caecal impactions, either with a typhlotomy or by-pass procedure. Aitken et al (2015) demonstrated in a single centre, retrospective case series that re-feeding did not differ between surgically or medically treated caecal impactions with the median time to first feed being 36 hours and median time to first hay being 72 hours [17]. There may be a variation of answers from respondents regarding reintroduction of feed and water for caecal impactions due to the sparse information in the reference texts [17].…”
Section: Accepted Articlementioning
confidence: 99%
“…2012; Aitken et al . 2015). Caecal impaction in hospitalised horses can go unrecognised if the horse’s mentation is altered because of the problem that required hospitalisation.…”
Section: Risk Factorsmentioning
confidence: 99%
“…1984; Moore and Hardy 2017), and as low as 25% (Aitken et al . 2015). Multiple classifications (primary or secondary, acute or chronic and type I or II) have been applied to caecal impactions (Sherlock 2019).…”
Section: Introductionmentioning
confidence: 99%